Traditional used Plants against Cognitive Decline and Alzheimer Disease - Eckert, Gunter P. (Frontiers in Pharmacology, 2010)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized clinically by progressive memory deficits, impaired cognitive function, and altered and inappropriate behavior. Aging represents the most important risk factor for AD and the global trend in the phenomenon of population aging has dramatic consequences for public health, healthcare financing and delivery systems in the word and, especially in developing countries. Mounting evidence obtained in in vitro and in vivo studies, suggests that various traditionally used plants in Asia, India and Europe significantly affect key metabolic alterations culminating in AD-typical neurodegeneration. The present article aims to bring the reader up-to-date on the most recent studies and advances describing the direct and indirect activities of traditional used plants and its constituents possibly relieving features of AD. A variety of traditional used plants and its extracts exerted activities on AD related drug targets including AChE activity antioxidative activity, modulation of Aβ-producing secretase activities, Aβ-degradation, heavy metal chelating, induction of neurotrophic factors and cell death mechanisms. Although pre-clinical investigations identified promising drug candidates for AD, clinical evidences are still pending.